«Smart Cities» of the debt crisis: grassroots creativity in Mediterranean Europe - Leontidou, Lila (The Greek Review of Social Research, 2015)
This paper challenges mainstream, neoliberal conceptualizations of the «Smart City» and the Incubator Hypothesis, by inserting grassroots creativity and solidarity into their logic. It is argued that the debt crisis in Southern Europe paves the way for a grassroots version of the Smart City, a city with hybrid public and common spaces, where the virtual and the material mingle, where grassroots creativity combines technology and knowledge, as it is largely based on massive ICT use and a highly educated young population. Typologies are constructed for several types of diverse collectivities, economies and productive initiatives. Top-down strategies of quasi-Orientalist stigmatization and suppression of every mobilization, alternative political discourse, imagination and creativity are sharply criticized as responsible for the crisis itself. Policy-oriented questions are posed and advocacy planning is explored in order to empower grassroots creativity in the context of digital societies.